PERCEPTION OF CANCER PATIENTS ON CHEMOTHERAPY SIDE EFFECTS - Rani Lisa Indra; Bayu Saputra (Poltekkes Kemenkes Semarang, 2021)
Chemotherapy causes various side effects that can affect the patient's physical or non-physical condition. Patients' perceptions or ratings of these side effects vary. This study aimed to identify cancer patients' perceptions of the side effects of chemotherapy they are undergoing. The descriptive study was conducted on 84 samples, namely cancer patients aged more than 20 years who had undergone chemotherapy at least once before. Data collection using a questionnaire that has been tested for validity and reliability. Data analysis was carried out descriptively with frequency distribution. The results showed that the perception of the physical side effects of chemotherapy that was considered very disturbing by the patient (severe symptoms) was nausea (59.5%), feeling of weakness (36.9%), hair loss (35.7%), vomiting. (29.8%), loss of appetite (28.6%). %), weight loss (27.4%), insomnia and skin discoloration (19% each), headache (16.7%) and fever (15.5%). When the perception of non-physical side effects was fear of death, affecting work/household duties and feeling fear (15.5% each), feeling anxious about my life, and the presence of family members I have to take care (14.3% each). The most disturbing side effects of chemotherapy are physical problems. The health service is expected to increase interventions to minimize the side effects of chemotherapy.